Exploring the Impact of ChatGPT in English Language Teaching-Learning Pedagogy - Aryal, Muna (Journal of NELTA Gandaki, 2024)
The integration of artificial intelligence (AI) tools like ChatGPT into English Language Teaching-Learning (ELTL) pedagogy represents a significant shift in education, promising personalized learning experiences and improved teaching methodologies. However, despite the growing importance of AI in education, there has been limited research on understanding the challenges and opportunities faced by teachers in effectively integrating AI tools like ChatGPT into their teaching practices. This study seeks to address this gap by examining the impact of ChatGPT on ELTL practices, focusing on the experiences of five English teachers. Using a qualitative research design, the study employed a phenomenological approach to explore the lived experiences of participants. Data were collected through semi-structured interviews, allowing in-depth exploration of teachers’ perceptions and experiences. Thematic analysis was used to examine the data. The results show that there are essential pedagogical and technological obstacles, including interface problems, connectivity issues, and the requirement for connection with curriculum objectives. Despite these challenges, the study presents fresh concepts and demonstrates how ChatGPT might improve language learning outcomes. The study highlights how crucial it is for teachers to get continuous support and assistance to fully utilize AI technology in language learning. The study suggests that to assist teachers in overcoming the difficulties related to ChatGPT integration, educational institutions should provide extensive training programs, online resources, and opportunities for peer collaboration. Therefore, further research is encouraged to deepen our understanding of ChatGPT’s integration into ELTL pedagogy and to empower teachers to navigate the evolving landscape of education technology effectively.